Peningkatan Kesadaran Masyarakat Terhadap Kesehatan Keluarga Melalui Penanaman Tanaman Obat Keluarga - Bintari Prasetiyasmara; Elfahmi Lubis; Septina Lisdayanti; Romadhona Kusuma Yudha (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Home gardens have enormous potential and can be used as a source of food supply with nutritional value and high economic value. Programs that can be utilized by the community to improve family welfare in the food sector are by planting family medicinal plants. Family medicinal plants are a collection of plants that are cultivated in the yard. The development and utilization of family medicinal plant cultivation is very necessary to support public health and create a green environment. its activities are carried out in an effort to provide learning experiences or create a condition for community behavior to increase public awareness of family health. The target audience for this health education activity are housewives in  Tanjung Anom Village, Giri Mulya District, North Bengkulu Regency.